2016
DOI: 10.3109/00498254.2016.1163753
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism study of saikosaponin d and its derivatives in rat liver microsomes

Abstract: 1. Saikosaponins, one of the representative bioactive ingredients in Radix Bupleuri, possess hepatoprotective, anti-inflammatory, antiviral, antitumor, and other pharmacological activities. Up to now, few studies focused on the further metabolism of saikosaponins and their secondary metabolites absorbed into the circulatory system. 2. To understand the in vivo efficacy of saikosaponin d, the in vitro metabolism of saikosaponin d, and its two derivatives formed in the gastrointestinal tract, prosaikogenin G and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…94 was clearly observed in VPBR, VPBR-VPPRA herb-pair, SNS-containing VPBR and VPPRA, and SNS, and almost undetectable in BR and BR-PRA herb-pair. According to the fragmentations in both positive and negative ion modes and other reports [22,23,24], we suggested that peak No. 94 is SSg.…”
Section: Resultssupporting
confidence: 52%
“…94 was clearly observed in VPBR, VPBR-VPPRA herb-pair, SNS-containing VPBR and VPPRA, and SNS, and almost undetectable in BR and BR-PRA herb-pair. According to the fragmentations in both positive and negative ion modes and other reports [22,23,24], we suggested that peak No. 94 is SSg.…”
Section: Resultssupporting
confidence: 52%
“…The metabolic routes are different depends on different administrative routes . The same research group also confirmed that, similar to SSa, SSd and its derivatives PSGG and SGG are all transformed into phase-1 metabolites through liver microsomeand CYP enzymes-mediated oxidation, including dehydrogenation, monooxidation, and carboxylation and combination of these processes on aglycone moiety (Yu et al, 2017).…”
Section: Metabolism Of Sssmentioning
confidence: 76%
“…Liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) was employed to simultaneously detect the contents of SSs (SSa, SSc and SSb2) in rat plasma (Xu et al, 2012b). Most recently, both SSa and SSd, as well as 15 and 16 metabolites, respectively, were simultaneously identified in various bio-samples, including plasma, bile, feces and urines, by using state-of-the-art liquid chromatography-diode array detector coupled with hybrid ion trap-time-of-flight mass spectrometry (LC-DAD-IT-TOF-MS) analysis Yu et al, 2017).…”
Section: Extraction and Identification Of Sssmentioning
confidence: 99%
“…However, it is the dissociation patterns in the positive ion mode which provide the direct structural information about aglycones that pose a great challenge to elucidate. For example, the challenge still exists in characterizing and identifying the in vitro metabolites of SSd even after the characterization and identification of the in vivo metabolites of its epimer, SSa, had been reported . Not surprisingly, it will become more difficult in the case of metabolism research when the herbal medicines containing Bupleurum species are administered.…”
Section: Lc/dad‐it‐tof‐ms Analysis Of Saikosaponins C a D B1 And Bmentioning
confidence: 99%